Improving Students’ Vocabulary Mastery by Using Short English Movie at the Eleventh Grade of SMA N 8 Kota Jambi - Nurul fitri (Universitas Batanghari Jambi, 2018)
AbstractThe purpose of this research is to find out students' vocabulary mastery by using the media short English movie. The experimental study involved eleventh high school students in SMA N 8 Kota Jambi. From 84 students who have two classes were selected as the study sample. The first class is class IPS 1 as experimental class and the second class is class IPS 4 as control class. After 2 sessions (within 2 weeks) post test is given. The researcher got the data from pre-test and post-test. In collecting data the instrument of this research is test. Based on the calculation of the statistical analysis, it is found that the value of t-test was 2.08 is higher than the value of t-table 1,67 it means Ha is accepted. Results of the data analysis have revealed that the teaching of English vocabulary by using media short English movie can improve students' vocabulary mastery.Keywords: Students’ vocabulary, short English movie.